Tocilizumab Contributes to the Inflammatory Status of Mature Dendritic Cells through Interleukin-6 Receptor Subunits Modulation - Meley, Daniel; Héraud, Audrey; Gouilleux-Gruart, Valerie; Ivanes, Fabrice; Velge-Roussel, Florence (Frontiers in Immunology, 2017)
Tocilizumab, a humanized anti-IL-6 receptor α (IL-6Rα), is widely used in the treatment of a panel of pathologies such as adult and juvenile rheumatoid arthritis and the systemic form of juvenile idiopathic arthritis in children. Its indications are expected to be largely extended to others inflammatory diseases in close future. Dendritic cells (DCs) appear to be deeply involved in the immunopathology of these diseases, yet the effects of tocilizumab on these cells were poorly studied. In the present study, we explored the effect of tocilizumab on the regulation of IL-6R subunits (gp130, sIL-6Rα and mIL-6Rα) in human monocyte-derived DCs. Human dendritic cells were derived from CD14+ monocytes purified with beads with IL-4 and GMCS-F. Ex vivo cultures of DCs were performed in the presence of tocilizumab. Using LPS maturation of DCs, we demonstrate that tocilizumab did not inhibit IL-6 secretion, enhanced mIL-6Rα expression and largely increased sIL-6Rα secretion. MAPK modulated STAT3 phosphorylation and surface expression of IL-6Rα in LPS-DCs. Tocilizumab had not impact on STAT3 phosphorylation in LPS-DCs while both LPS and IL-6 increased its activation. Tocilizumab modulated the regulation of IL-6R subunits leading to an inflammatory status of DCs and a massive secretion of IL-6Rα. Our results demonstrate that DCs acquire a pro-inflammatory profile following tocilizumab treatment, becoming a major source of IL-6 trans-signalling activation that might explain the poor clinical benefit in some RA patients.